Mathematical Reasoning Ability of Male and Female Students in Problem Base Learning - Negara, Habibi Ratu Perwira (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
Considering the objectives and standards of the mathematics learning process, mathematical reasoning is an ability that students are expected to have. Nonetheless, the mathematical reasoning abilities of Indonesian students are still inadequate, and learning resources are still inadequate. The researcher then tries to solve it by combining the problem-based learning (PBL) paradigm with the use of GeoGebra in the classroom. The aim of this research is to identify and analyze the effect of GeoGebra and Gender-assisted problem-based learning (PBL) models on students' mathematical reasoning abilities. The study involved 35 students of XI State Senior High School at one of the schools in Mataram City. The research instrument used a mathematical reasoning ability test consisting of five essay questions. The study applied a one-group pretest-posttest design to observe the increase in students' mathematical reasoning abilities. Mathematical reasoning ability tests were given before and after the implementation of the GeoGebra-assisted PBL model. Data analysis used descriptive statistics, paired t-tests, and independent t-tests. The results of the analysis show that improving students' mathematical reasoning abilities can be done by applying the GeoGebra-assisted PBL model in the classroom. Observation of the psychological aspects of Gender showed significant results in students' mathematical reasoning abilities.